2004
DOI: 10.1063/1.1803541
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial stability of electrodeposition of cuprous oxide films

Abstract: Experiments on deposition of Cu(2)O films from basic copper sulfate solution show that copper also deposits. At low, but basic values of pH only copper deposits and at high pH only cuprous oxide deposits. In the intermediate range where both compete the system shows oscillations at "constant current." Linear stability analysis has been conducted for such an electrochemical cell to show that oscillations can take place in the parameter space identified in the experiments. The results are keeping with most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…During galvanostatic Cu 2 O deposition, copper metal codeposition is characterized by large oscillations of the electrode potential at fixed current, due to localized pH variations. 40,41 In order to achieve higher growth rates, therefore higher deposition currents, the temperature must be increased. This corresponds to increasing the slope of the phase-boundary lines in the Pourbaix diagram according to the Nernst equation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During galvanostatic Cu 2 O deposition, copper metal codeposition is characterized by large oscillations of the electrode potential at fixed current, due to localized pH variations. 40,41 In order to achieve higher growth rates, therefore higher deposition currents, the temperature must be increased. This corresponds to increasing the slope of the phase-boundary lines in the Pourbaix diagram according to the Nernst equation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The potential oscillates with time. Linear stability analysis by Neogi [53] has shown that Cu 2 O and Cu are deposited alternately along the face of the cathode with dendrite formation superimposed on these. Zhong et al [54] have removed the formation of dendrites in electrodeposition in this system by reducing the width of the cell to $200 nm.…”
Section: Additives and Competing Reactionsmentioning
confidence: 98%
“…The reasons Cu 2 O is considered a potential solar-driven photocatalyst are as follows: (i) it is nontoxic; (ii) it is composed of two very abundant elements; (iii) it has a good absorption coefficient for light with wavelength above 580 nm [33] and high theoretical solar cell conversion efficiency (up to 18%) [34]; and (iv) it is easy to prepare. Stability of Cu 2 O has been studied by some researchers [36][37][38][39][40][41]. Stability of Cu 2 O has been studied by some researchers [36][37][38][39][40][41].…”
mentioning
confidence: 99%